Altered local gyrification and functional connectivity in type 2 diabetes mellitus patients with mild cognitive impairment: A pilot cross-sectional small-scale single center study - Shao, Pengfei; Li, Xin; Qin, Ruomeng; Xu, Hengheng; Sheng, Xiaoning; Huang, Lili; Ma, Junyi; Cheng, Yue; Chen, Haifeng; Zhang, Bing; Zhao, Hui; Xu, Yun (Frontiers in Aging Neuroscience, 2022)
Aims: The present research aimed to explore alterations in the local gyrification index (GI) and resting-state functional connectivity (RSFC) in type 2 diabetes mellitus (T2DM) patients with mild cognitive impairment (MCI). Methods: In this study, 126 T2DM patients with MCI (T2DM-MCI), 154 T2DM patients with normal cognition (T2DM-NC) and 167 healthy controls (HC) were recruited. All subjects underwent a battery of neuropsychological tests. A multimodal approach combining surface-based morphometry (SBM) and seed-based RSFC was used to determine the structural and functional alterations in T2DM-MCI patients. The relationship among the GI, RSFC, cognitive ability, and clinical variables was characterized. Results: Compared with T2DM-NC group and HC group, T2DM-MCI patients showed significantly reduced GI in bilateral insular cortex. Decreased RSFC was found between left insula and right precuneus, and right superior frontal gyrus (SFG). The altered GI was correlated with T2DM duration, global cognition, and episodic memory. The mediating effects of RSFC on the association between GI and cognition was not statistically significant. Conclusion: Our results suggested that GI may serve as a novel neuroimaging biomarker to predict T2DM-related MCI and help us to improve the understanding of the neuropathological effects of T2DM-related MCI.